Seasonal Variations and Drivers of Surface Ocean pCO2 in the Seasonal Ice Zone of the Eastern Indian Sector, Southern Ocean. Issue 1 (27th December 2021) - Tozawa, Manami; Nomura, Daiki; Nakaoka, Shin‐ichiro; Kiuchi, Masaaki; Yamazaki, Kaihe; Hirano, Daisuke; Aoki, Shigeru; Sasaki, Hiroko; Murase, Hiroto
Abstract: To quantitatively assess the inorganic carbon cycle in the eastern Indian sector of the Southern Ocean (80–150°E, south of 60°S), we measured ocean surface temperature, salinity, total alkalinity (TA), the partial pressure of carbon dioxide (pCO2 ), and concentrations of chlorophyll‐ a (chl a ), dissolved inorganic carbon (DIC), and nutrients during the KY18 survey (December 2018–January 2019). The sea–air CO2 flux in this region was −8.3 ± 12.7 mmol m −2 day −1 (−92.1 to +10.6 mmol m −2 day −1 ). The ocean was therefore a weak CO2 sink. Based on the DIC and TA in the temperature minimum layer, we estimated the change of pCO2 from winter to summer (δpCO2 ) due to changes in water temperature, salinity, and biological activity (photosynthesis). The spatial distribution of pCO2 in the western part (80–110°E) of the study area was mainly driven by biological activity, which decreased pCO2 from December to early January, and in the eastern part (110–150°E) by temperature, which increased pCO2 from January to February. We also examined the changes in the CO2 concentrations (xCO2 ) over time by comparing data from 1996 with our data (2018–2019). The oceanic and atmospheric xCO2 increased by 23 and 45 ppm in 23 years, respectively. These changes of ocean xCO2 were mainly driven by an increase in CO2 uptake from the atmosphere as a result of the rise in atmospheric xCO2 and increase in biological activity associated with the change in the water‐mass distribution. Plain Language Summary: Determining the drivers of seasonal changes in ocean CO2 is important for estimating the global carbon cycle. Seawater samples were collected in the eastern Indian sector of the Southern Ocean to investigate the carbonate chemistry of the ocean surface water. During winter and summer, the partial pressure of carbon dioxide (pCO2 ) at the ocean surface decreased and increased due to photosynthesis and temperature changes, respectively. Surface water pCO2 was lower than the pCO2 of the atmosphere in summer: the result was CO2 uptake by the ocean. A comparison of data from 1996 with our data (2018–2019) indicated that the CO2 concentration (xCO2 ) of the seawater had increased by 23 ppm. This increase was due primarily to an increase in uptake of CO2 from the atmosphere as a result of the rise of atmospheric xCO2 . Key Points: The eastern Indian sector of the Southern Ocean absorbs atmospheric CO2 weakly in summer Biological activity and increases in water temperature change the pCO2 from winter to summer Changes in atmospheric pCO2 and water masses explained the interannual variations of dissolved CO2 in the ocean